Brain metastasis in a patient with melanoma receiving Pembrolizumab therapy: A case report and review of the literature. Issue 50 (December 2017) - Song, Jin-cheng; Ding, Xiao-lei; Sun, Xiu-hua; Safi, Mohammed; Tian, Juan
Abstract: Rationale: Melanoma with brain metastasis is associated with a poor prognosis and high mortality rate. As patients with this condition have been excluded from most clinical trials, data on the use of anti–programmed death 1 therapy for these patients are limited. Patient concerns: The patient was a 62-year-old man with a 10-year history of melanotic nevus in his right forearm. He was admitted to another hospital in August 2015 due to the growth of the melanotic nevus over 1 year and complaint of a mass in the right mid-axillary area. The patient had no relevant medical, surgical, or family history. Diagnoses: The biopsy of his right axillary lymph node showed malignant melanoma. Interventions: He was subsequently treated with adjuvant high-dose interferon after dacarbazine. Numerous metastatic lesions were found in his lung, abdomen, pelvic cavity, and brain after five months later, and then Pembrolizumab was used for six cycles (2 mg/kg every 3 weeks). He experienced immunorelated adverse events and we gave him cortisol to treat immunorelated disease until pneumonia was found. Outcomes: We observed a delayed effect after three cycles of Pembrolizumab, the intracranial lesion presented clear margins and localization, while the other lesions became much smaller. A mixed response was observed after four cycles, with still stable extracranial metastases but growing a new lesion in brain. After two additional cycles of Pembrolizumab, the treatment was stopped due to the patient's inability to pay for it and a decline in his performance status. He then received palliative treatment at a local hospital and died for severe pulmonary infection, with an overall survival time of 7 months from metastasis. Lessons: In the case reported here, a delayed and mixed response was observed after Pembrolizumab was used. Because of causing severe pulmonary infection, the use of steroids should be considered carefully when treating immunorelated adverse events. It seemed that the Pembrolizumab has a positive effect on melanoma brain metastases especially combined with other treatments. However, there are still some challenges including patient selection, predictors of response, drug tolerance, optimizing combination strategies and control of adverse effects. More carefully designed clinical trials are urgently needed.